2013
DOI: 10.1371/journal.pone.0075928
|View full text |Cite|
|
Sign up to set email alerts
|

Biodegradation of the Allelopathic Chemical m-Tyrosine by Bacillus aquimaris SSC5 Involves the Homogentisate Central Pathway

Abstract: m-Tyrosine is an amino acid analogue, exuded from the roots of fescue grasses, which acts as a potent allelopathic and a broad spectrum herbicidal chemical. Although the production and toxic effects of m-tyrosine are known, its microbial degradation has not been documented yet. A soil microcosm study showed efficient degradation of m-tyrosine by the inhabitant microorganisms. A bacterial strain designated SSC5, that was able to utilize m-tyrosine as the sole source of carbon, nitrogen, and energy, was isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Our studies showed that the expression 3 of these miRNAs was greatly increased in BYG treated with different phenolic acids. Microorganisms, an important link between allelochemicals and target plants, have 9 received increasing attention (Bertin et al 2003;Blum 2003;Dayan et al 2010;10 Inderjit 2005;Khan et al 2013;Zuo et al 2014), and the biotransformation of 11 allelochemicals by particular environmental microorganisms has been reported to be 12 necessary and to contribute to an increase in allelopathy (Wang et al 2013). In this 13 study, a specific microbe, the Myxococcus species, showed a close relationship with 14 rice allelopathic inhibition.…”
Section: Accepted Articlementioning
confidence: 75%
“…Our studies showed that the expression 3 of these miRNAs was greatly increased in BYG treated with different phenolic acids. Microorganisms, an important link between allelochemicals and target plants, have 9 received increasing attention (Bertin et al 2003;Blum 2003;Dayan et al 2010;10 Inderjit 2005;Khan et al 2013;Zuo et al 2014), and the biotransformation of 11 allelochemicals by particular environmental microorganisms has been reported to be 12 necessary and to contribute to an increase in allelopathy (Wang et al 2013). In this 13 study, a specific microbe, the Myxococcus species, showed a close relationship with 14 rice allelopathic inhibition.…”
Section: Accepted Articlementioning
confidence: 75%
“…In previous studies, B. aquimaris has been demonstrated to degrade various pollutants, including microplastics [48,49]. This strain can be isolated from soil or marine environments and is commonly found in the environment [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we found that some congeneric species showed a close interaction with allelochemicals. For instance, Pseudomonas catalysed (-)-catechin conversion into 3,4-dihydroxybenzoic acid, and 3,4-dihydroxybenzoic acid showed a higher phytotoxicity than (-)-catechin (Masuda et al 2007); Bacillus aquimaris involved in the degradation of allelopathic m-tyrosine (Khan et al 2013); F. oxysporum, a replant disease pathogen in P. heterophylla rhizospheric soil, increased sharply under a consecutive-replant system, and some phenolic acids promoted the growth of F. oxysporum f.sp. (Zhao et al 2015).…”
Section: Discussionmentioning
confidence: 99%